Evaluasi Penerimaan dan Pengalaman Pengguna Platform SMArt LMS Menggunakan Integrasi Metode TAM dan Analisis Deskriptif Kualitatif - Mahmudin; Muhidin (UNISTEK, 2026)
The SMArt LMS platform is a strategic infrastructure implemented by the Directorate of Senior High Schools to support the digitalization of education in Indonesia. This study aims to evaluate user acceptance and experience of SMArt LMS using an integration of the Technology Acceptance Model (TAM) and qualitative descriptive analysis. Data were collected from 1,718 participants of the Technical Guidance (Bimtek) program across nine regions. Quantitative analysis showed high reliability for the instruments, with Cronbach?s Alpha values exceeding 0.60, specifically 0.966 for the Perceived Ease of Use (PEOU) construct. Qualitative triangulation revealed that discussion features and Follow-up Plan (RTL) instructions significantly assisted material comprehension. However, technical aspects such as access stability across various devices still require optimization. This research provides strategic recommendations for platform managers to develop LMS features that are more adaptive and aligned with the digital ecosystem in high school environments.